Management control for start-up companies – fragmented efforts or a unified framework? - Dyczkowski, Tomasz; Dyczkowska, Joanna (Research Papers of Wrocław University of Economics, 2018)
The rationality of implementing management control in start-ups has not been confirmed in research studies so far. On the contrary, it was suggested that formality may negatively affect innovativeness of a business. Despite a scarcity of positive evidence, the authors initiated research testing whether managers and employees witnessed benefits of MC to start-ups. The study was conducted on a sample of 45 enterprises. It showed, that although only 4 companies appointed a controller, over a half of the sample monitored effectiveness of work, production or services and installed cost or quality management. The start-ups appreciated use of non-financial ratios in their performance management. Finally, lower intensity of using MC methodology was not observed among the youngest companies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 76-92
Keywords: management control; start-up company; controlling; przedsiębiorstwa start-up